HIV/AIDS knowledge, awareness and perception of undergraduate students at the University of Stellenbosch - Cornelissen, Gareth Mark (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2005.